2003
DOI: 10.3989/scimar.2003.67s213
|View full text |Cite
|
Sign up to set email alerts
|

Managing seabird metapopulations in the Mediterranean: constraints and challenges

Abstract: SUMMARY: In recent times metapopulation models have contributed important insights to conservation, and they have inspired field studies that focus on collecting key data on demography and movement. Seabirds are suitable models for studying ecological processes in metapopulations because they breed in discrete local populations (i.e. colonies) both in space and time. However, in the Mediterranean, seabird colonies mostly show conservation problems at an ecosystem level, linked to human activities (e.g. fisheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…This appears to be the case for our population, given the recorded drop in YLG body condition (Steigerwald et al 2015) along with a slight decrease in local survival rates after landfill closure. Gulls usually form spatially structured populations and given that previous studies have shown that dispersal occurs following environmental perturbations (Oro et al 2004, Ferna´ndez-Chaco´n et al 2013, we suggest that food limitation has triggered not only mortality but also permanent emigration (through breeding dispersal) to neighboring populations (Bosch 2000, Oro 2003.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be the case for our population, given the recorded drop in YLG body condition (Steigerwald et al 2015) along with a slight decrease in local survival rates after landfill closure. Gulls usually form spatially structured populations and given that previous studies have shown that dispersal occurs following environmental perturbations (Oro et al 2004, Ferna´ndez-Chaco´n et al 2013, we suggest that food limitation has triggered not only mortality but also permanent emigration (through breeding dispersal) to neighboring populations (Bosch 2000, Oro 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence clearly shows one thing, at least: local population changes may affect other local populations, even quiet far. Therefore, local actions (as breeding facilitation of endangered species or culling of considered pest species) need to consider the global effect (see Oro, 2003). Outside the reproductive season, most Mediterranean seabirds move to the Atlantic Ocean (see in this volume Mouriño et al, 2003;Valeiras, 2003;Yésou, 2003; see also Le Mao and Yésou, 1986) where only international fishing convenes would permit conservation measurements.…”
Section: Diagnosing Conservation Problems In the Mediterraneanmentioning
confidence: 99%
“…Here, predator numbers are limited and vegetation is kept at the pioneer stage, which enables adults to spot potential dangers more readily. Yet another important factor that determines breeding success is availability of food in the surrounding waters (Stienen et al 2000;Stienen and Brenninkmeijer 2002;Oro 2003). Thus, both nest safety and fish availability largely determine a colony's success.…”
Section: Introductionmentioning
confidence: 99%
“…The few birds that do not return to their original breeding site, nesting instead at an alternative location, can be regarded as dispersing animals. A number of connected breeding sites is called a metapopulation (Spendelow et al 1995;Akçakaya et al 2003;Oro 2003;Serrano and Tella 2003). Opdam (1991) described metapopulations as spatially structured populations of plants or animals consisting of distinct units (subpopulations), separated by space or barriers and connected via dispersal movements.…”
Section: Introductionmentioning
confidence: 99%